Penggunaan Metode Kartu Bergambar Untuk Meningkatkan Kemampuan Membaca Iqro’ Pada Anak Usia Dini di PAUD Al-Ikhlasyiah - Nurhalima (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study is motivated by several problems identified in the teaching of Iqro’ reading to early childhood learners, particularly the low mastery of hijaiyah letters due to unengaging learning activities, the inappropriate use of imitation techniques, the absence of instructional media, and suboptimal teaching strategies that make it difficult for children to retain the material. The research employed a Classroom Action Research (CAR) design to directly observe the teaching–learning process at PAUD Al-Ikhlasyiah Tampak Lobang, complemented by interviews to gather additional information. The focus of the study is to examine the effectiveness of using illustrated hijaiyah letter cards in improving the Iqro’ reading ability of children aged 5-6 years. The pre-cycle results showed that out of 12 children, 9 (75%) were categorized as not yet developing, and 3 (25%) were beginning to develop. None of the children reached the categories of developing as expected or developing very well. In Cycle I, after the implementation of the letter-card media, improvements were observed: in the first meeting, all children (100%) were in the beginning-to-develop category, while in the second meeting, 9 children (75%) were beginning to develop and 3 children (25%) had developed as expected. As the improvement was not optimal, the research proceeded to Cycle II. In Cycle II, the improvement became significant. In the first meeting, 1 child (8.3%) was in the beginning-to-develop category, 9 children (75%) had developed as expected, and 2 children (16.7%) had developed very well. In the second meeting, no children remained in the not-yet-developing or beginning-to-develop categories; 4 children (33.3%) developed as expected and 8 children (66.7%) developed very well. Classically, mastery reached 66.7%. The study concludes that the use of illustrated hijaiyah letter cards is effective in improving the Iqro’ reading ability of children aged 5-6 years at PAUD Al-Ikhlasyiah.